Struktur Vegetasi di Habitat Ulin (Eusideroxylon zwageri) Cagar Alam Durian Luncuk II - Khoiriyah, Zhulfatul; Maharani, Shinta; Nopita, Melni; Sazali, Ahmad (Universitas Bengkulu, 2024)
Ulin (Eusideroxylon zwageri) is a species from the family of Lauraceae. Additionally, the plant is referred to as